Looking up Prescriptions to Treat Infectious Disease: Anti-epidemic Books of Medical Formularies and Epidemic Prevention and Control in the Qing Dynasty - Xiyang LIU (Chinese Medicine and Culture)
Copying, compiling, publishing, disseminating, and referencing anti-epidemic books of medical formularies were common activities during the outbreak of epidemics in the Qing dynasty. Its emergence, motivated by epidemic disease again and again, was important component parts of epidemic prevention and control. They played a unique role as media on affairs such as treating patients suffering from infectious diseases, mobilizing peoples to make contributions to anti-epidemic activities, integrating and popularizing knowledge of epidemic prevention. Anti-epidemic books of medical formularies were important to link peoples, things, and substances related with epidemic prevention and control, and were a kind of motivation to actively deal with the infectious disease, control the epidemic, and maintain health. Compared to other common measures, anti-epidemic books of medical formularies participated in many prevention and control practices deeply, which actually built a low cost, spontaneous, dispersed and non-institutional system to respond to epidemic, and the system had characteristics of stronger conductibility, bigger coverage area, and better external benefits.